The green man enigma: Unique presentation of toxicology in the emergency department. Issue 5 (5th September 2021) - Trotzky, Daniel; Pachys, Gal; Zarror, Amir; Mosery, Jonathan; Cohen, Aya; Shaheen, Khieralla; Kalmanovich, Eran; Ilgiyaev, Eduard; Goltsman, Galina
Abstract: We describe a case report of hypertensive crisis induced by a combination of amphetamine and Marwitt's Kidney Pills. Diagnosis was delayed because of nonspecific physical findings including chest pain, abdominal pain, coughing, and diarrhea. This was confounded by puzzling physical examination findings, including green‐colored urine and fingernails. Diagnosis was aided with point‐of‐care ultrasound, which presented a picture of acute cardiac insufficiency, pulmonary congestion, and bilateral effusions. Laboratory values on admission indicated acute multiorgan injury. Detailed patient history revealed chronic consumption of "Kidney, " an over‐the‐counter drug available in Thailand with the primary ingredient methylene blue and used for a myriad of renal and genitourinary conditions. The patient also had a history of amphetamine use, which ultimately initiated his acute presentation.